Measuring the Entrepreneurial Intention Among Millennials in Uttarakhand - Agarwal, Richa; Singh, Sricha; Pokhriyal, A. K. (AMC Indian Journal of Entrepreneurship, 2020)
In a developing country like India, most of the millennials intend to be employees in a company rather than start their own enterprise. The present study aimed at unfolding the reasons behind development of entrepreneurial intention and did not concern with the relation between intention and action. A well-structured questionnaire on a five-point Likert scale has been used for the measurement of entrepreneurial intention. The factors included in the study are attitude towards entrepreneurship, instrumental readiness, locus of control, subjective norms, need for achievement, and perceived support and barriers. The data were analysed with multiple regression. A positive relationship was found with locus of control, subjective norms, and instrumental readiness of various age groups where parent’s occupation is a major hindrance to starting a own venture. The findings will help the government to address the emerging issue of unemployment among millennials. The results of the study will classify the factors which play a significant role in influencing students’ entrepreneurial mindset in the mountainous state of Uttarakhand.